Activating and Enhancing the Energy Flexibility Provided by a Pipe-Embedded Building Envelope: A Review - Xiaochen Yang; Yanqing Li; Xiaoqiong Li; Khaled A. Metwally; Yan Ding (Buildings)
Building thermal mass offers a cost-effective solution to enhance the integration of energy supply and demand in dynamic energy systems. Thermally activated building systems (TABS), incorporating embedded heat tubes, shows strong potential for energy flexibility. However, the significant thermal inertia of TABS also imposes challenges to precise load shift and indoor climate control. This review synthesizes key research on the effective demand-side management of TABS from multiple perspectives. It examines and compares various TABS configurations, including floor, ceiling, and wall systems. Differences in heat transfer performance between heating and cooling result in distinct application preferences for each type. The integration of advanced materials, such as phase change materials (PCM), can further enhance energy flexibility. TABS flexibility is primarily activated through adjustments to indoor operative temperature, with relevant influencing factors and regulatory constraints analyzed and discussed. Key aspects of optimizing building energy flexibility, including simulation methods and control strategies for TABS, are reviewed from both theoretical and practical perspectives. The energy and economic performance of TABS under various control strategies is analyzed in detail. This review provides insights to support the optimal design and operation of TABS within dynamic energy systems and to enhance the energy flexibility of building envelopes.